VDTNsim: a simulation tool for vehicular delay-tolerant networks - Soares, V.N.G.J. (2010)
Developing an adequate network architecture for supporting data communications in vehicular networks is critical to overcome the challenges caused by highly dynamic network topology, connectivity disruption, and intermittent connectivity issues. Among several approaches available in the literature proposed to address these problems, vehicular delay-tolerant networking (VDTN) architecture appears as a recent and innovative solution that integrates the concepts of end-to-end, asynchronous, and variable-length bundle oriented communication; Internet protocol over VDTN; and out-of-band signaling. VDTN architecture, protocols and services are in a fairly early stage of development. Therefore, simulation appears as an important tool providing a highly flexible, low-cost, and fast answer for research questions, and furnishes important inputs for exploring through prototyping. This paper presents and describes the proposal and construction of a simulation tool for VDTN networks, called VDTNsim.